Digital Law Enforcement and Public Trust in Pasuruan’s E-Ticketing System - Muhammad Yudhi Iswanto; Misranto Misranto; Sunardi Sunardi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The modernization of traffic law enforcement in Indonesia marks a transition from conventional to digital systems through electronic ticketing (e-tilang), reflecting the state’s adaptation to technological and social transformations. Specific Background: Police Regulation Number 2 of 2025 introduces electronic evidence-based enforcement to enhance transparency, efficiency, and accountability in traffic management within the jurisdiction of the Pasuruan Regency Police. Knowledge Gap: Despite its normative strength, the practical effectiveness of this regulation remains unclear, especially regarding its harmony with social dynamics, legal culture, and local infrastructure readiness. Aims: This study examines the legal effectiveness of e-ticketing implementation in Pasuruan Regency by analyzing the interrelation between legal norms, enforcement structures, and public awareness. Results: Findings reveal that while e-ticketing aligns with the legality principle and reduces extortion, its effectiveness is constrained by limited infrastructure, low digital literacy, and weak cross-agency coordination. Novelty: This research highlights e-ticketing as not merely an administrative reform but a moral-legal transformation emphasizing justice, empathy, and public trust in digital law. Implications: Strengthening legal literacy, enhancing interagency integration, and promoting participatory education are essential for realizing a humane, transparent, and just digital legal system. Highlights: Examines how technology transforms traditional law enforcement into digital systems. Identifies key barriers such as limited infrastructure and low digital literacy. Emphasizes the need for human-centered, just, and transparent digital law practices. Keywords: Legal Effectiveness, E-Ticketing, Digital Law Enforcement, Traffic Justice